THE ROLE OF INTELLIGENT TRANSPORTATION SYSTEMS IN IMPLEMENTING AUTOMATED PAYMENT SYSTEMS ON TOLL ROADS - Muminov Kurbon; Yadgarov Sirojiddin; Kuchkorov Doston (Modern American Journals, 2025)
As a continuation of the recent developments in the road infrastructure sector in our country, the construction of toll roads such as the Tashkent–Samarkand and Tashkent–Andijan highways is of great importance. One of the key issues in toll road operations is the automation of payment systems for vehicles.This article examines modern approaches to implementing automated toll collection systems and highlights the role of Intelligent Transportation Systems (ITS) in this process. The study analyzes how ITS contributes to optimizing traffic flow, simplifying the payment process, and increasing the overall efficiency of road infrastructure. Proposals and conclusions are presented based on both local and international experiences.
Keywords: Toll roads, traffic intensity,